Motor imagery and tennis serve performance: The external focus efficacy - Guillot, A.; Desliens, S.; Rouyer, C.; Rogowski, I. (Journal of Sports Science & Medicine, 2013)
There is now ample evidence that motor imagery (MI) contributes to enhance motor performance. Previous research also demonstrated that directing athletes' attention to the effects of their movements on the environment is more effective than focusing on the action per se. The present study aimed therefore at evaluating whether adopting an external focus during MI contributes to enhance tennis serve performance. Twelve high-level young tennis players were included in a test-retest procedure. The effects of regular training were first evaluated. Then, players were subjected to a MI intervention during which they mentally focused on ball trajectory and specifically visualized the space above the net where the serve can be successfully hit. Serve performance was evaluated during both a validated serve test and a real match. The main results showed a significant increase in accuracy and velocity during the ecological serve test after MI practice, as well as a significant improvement in successful first serves and won points during the match. Present data therefore confirmed the efficacy of MI in combination of physical practice to improve tennis serve performance, and further provided evidence that it is feasible to adopt external attentional focus during MI. Practical applications are discussed.